Enhancing thermal conductivity and toughness of cellulose nanofibril/boron nitride nanosheet composites. (15th November 2022) - Xu, Ying; Chen, Xinrui; Zhang, Caixia; Ragauskas, Arthur J.; Wen, Jia-Long; Zhao, Peitao; Si, Chuanling; Xu, Ting; Song, Xueping
Abstract: Generally, the thermal conductivity ( TC ) of composite based on cellulose nanofibrils (CNF) is improved by adding thermal conductive filler, which inevitably leads to the loss of its mechanical properties. In this work, it is the first to simultaneously improve the toughness and TC of CNF/boron nitride nanosheets (BNNS) composite from the perspective of thermal conductive filler addition and CNF crystal change. The hydrophilic-modified BNNSs were successfully prepared by xylose-assisted ball-milling prior to adding into CNF. Compared with that of CNF film (1.34 W/(m·K)), the in-plane TC of CNF/BNNS composite (12.68 W/(m·K)) increased significantly by 846 % with loading 30 % BNNS. Afterwards, both toughness (8.0 MJ·m −3, increased ~250 %) and TC (14.7 W/(m·K), increased ~16 %) of CNF/BNNS composite were further enhanced significantly by mercerization with 12.5 % NaOH solution. The simultaneously improvement of toughness and TC is unprecedented in related studies, which contributes to the effective preparation of thermal management materials. Graphical abstract: Unlabelled Image